BaMn9II(VO4)6(OH)2: a homospin ferrimagnet with a broken spinel-lattice of B-sites. Issue 14 (10th November 2014) - Guo, Wenbin; He, Zhangzhen; Tang, Yingying; Zhang, Suyun; Yang, Ming; Cheng, Wendan
Abstract : A new homospin ferrimagnet BaMn9 II (VO4 )6 (OH)2 exhibits a unique structural feature with a reverse triangular dipyramid Mn7 spin lattice, in which such a lattice can be considered as a broken spin lattice of B-sites in spinel compounds. Abstract : A new vanadate of BaMn9 II (VO4 )6 (OH)2 was synthesized by a conventional hydrothermal method. BaMn9 II (VO4 )6 (OH)2 crystallizes in the cubic space group Pa 3̄, which exhibits an edge-sharing MnO6 octahedral network structure with cavities occupied by Ba(VO4 )6 16− groups. The lattice built by Mn 2+ ions shows the reverse triangular dipyramid Mn7 in the system, which can be considered as a broken spin lattice of B-sites in spinels. The title compound shows a ferrimagnetic behavior with T C = 18 K.